2016
DOI: 10.1186/s40536-016-0020-8
|View full text |Cite
|
Sign up to set email alerts
|

Is computer availability at home causally related to reading achievement in grade 4? A longitudinal difference in differences approach to IEA data from 1991 to 2006

Abstract: BackgroundIs the level of home computer use causally related to reading achievement? This question is addressed in this paper theoretically, methodologically, and empirically through secondary analyses of data from reading literacy studies conducted by the IEA in 1991, 2001, and 2006. Based on previous analyses of aggregated country-level data (Rosén and Gustafsson 2014), our hypothesis is that increased computer use at home has a negative effect on reading achievement and that this can be explained by displa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
11
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(13 citation statements)
references
References 37 publications
1
11
0
1
Order By: Relevance
“…It therefore seems as if these differences in ICT user profiles do not necessarily lead to differences in CIL achievement. This result sheds light on the often controversially discussed relation between ICT use outside of school and student achievement (Rosén & Gustafsson, 2016;Tamim et al, 2011). In fact, the ICILS 2013 study did not reveal substantial relations among students' ICT use and their CIL achievement in Norway (Fraillon et al, 2014); hence, it seems somehow expected that the profiles, which are identified on the basis of ICT use variables, do not differentiate by CIL achievement.…”
Section: Differences In Cil Achievement Across Profiles (Rq 3)mentioning
confidence: 62%
“…It therefore seems as if these differences in ICT user profiles do not necessarily lead to differences in CIL achievement. This result sheds light on the often controversially discussed relation between ICT use outside of school and student achievement (Rosén & Gustafsson, 2016;Tamim et al, 2011). In fact, the ICILS 2013 study did not reveal substantial relations among students' ICT use and their CIL achievement in Norway (Fraillon et al, 2014); hence, it seems somehow expected that the profiles, which are identified on the basis of ICT use variables, do not differentiate by CIL achievement.…”
Section: Differences In Cil Achievement Across Profiles (Rq 3)mentioning
confidence: 62%
“…One possible reason for increased ICT use being related to a decrease in science and mathematics achievement in various analyses, is the notion that since digital tools are "fragmented communicators", they could be associated with poorer reading literacy, as communicated by Rosén (2011). In fact, a longitudinal international analysis at the country level by Rosén and Gustafsson (2016) has revealed a negative relationship between ICT availability and reading achievement for Grade 4 pupils.…”
Section: Integrating Digital Tools Into Technology Educationmentioning
confidence: 99%
“…For example, the Trends in International Mathematics and Science Study (TIMSS) was introduced in 1995 to assess educational outcomes in primary, secondary, and upper secondary school, and it is repeated in a four-year cycle. With such complex study designs, researchers can exploit variation across multiple educational stages (e.g., Hanushek & Woessmann, 2006) and over time (Rosén & Gustafsson, 2016). Moreover, they allow researchers to apply so-called "fixed-effects models" to make causal claims about the effects of certain features of the educational system on educational outcomes (see Schlotter, Schwerdt, & Woessmann, 2011, for a discussion of the methodological advantages of such research designs).…”
Section: Purposes Of Linkingmentioning
confidence: 99%
“…The goal of this study was to examine the causal effect of computer availability at home and reading achievement for fourth grade students. Specifically, Rosén and Gustafsson (2016) investigated the relation between changes in computer availability and changes in students' reading achievement between 1991 and 2006 in order to disentangle causal effects and interaction effects with students' background.…”
Section: Consequences Of Technological Change For Reading Achievementmentioning
confidence: 99%
See 1 more Smart Citation